Beyond the game: How social interaction and emotional gratification drive Chinese sports podcast engagement - Fangni Li (PLoS ONE, 2025)
The rapid growth of podcasting platforms has transformed digital media consumption, offering diverse content tailored to user preferences. The present research aims to identify the needs associated with engaging with sports podcasts on the Himalaya platform while exploring cognitive, emotional, and social satisfactions. Quantitative and qualitative data collection techniques used the Uses and Gratifications Theory (UGT) in the present research, including semantic network analysis, co-word clustering, and high-frequency words, to analyze the data collected from 13,692 comments of five popular sports podcast channels. The study shows that information seeking is the primary reason listeners tune in: they want game breakdowns and insiders’ opinions. This is further reinforced by self-efficacy and media convenience, which are important factors in the platform mandate of enabling users and assimilating content into their daily lives. First, the paper adds to scholarship by employing the UGT in the context of sports podcasts in China. Secondly, it provides valuable recommendations for practical use by content creators and platform developers. Overall, the results show the versatility of podcast consumption, although restrictions concerning demographic categorization and comparison with other media forms signal to undertake future studies. Such insights are relevant to improving and encouraging user interactions and how the platform delivers podcasts.